A shock to the (food) system: Using new IFPRI tools to evaluate household food security outcomes - Comstock, Andrew; Ecker, Olivier; Jones, Eleanor (International Food Policy Research Institute, 2024)
Recent crises and shocks have eroded food security in many countries. These crises take many forms. Some are global shocks, such as a sharp rise in food commodity prices in world markets. Some are local shocks—for instance, flooding from an extreme weather event, or another from the ever-increasing list of climate impacts.